2018
DOI: 10.1007/s10661-018-7035-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of wastewater treatment plants based on the emissions of microbiological contaminants

Abstract: This article presents the current and important results of bioaerosol studies which allow for the comparison of microbial contamination of air in 11 wastewater treatment plants (WWTPs), which differed in terms of capacity from 350 to 200,000 m3/day. The abundance of mesophilic bacteria, M+ and M− Staphylococcus, Pseudomonas fluorescens, Actinobacteria, coliform and psychrophilic bacteria, and microscopic fungi was determined. Additionally, the air temperature, relative humidity, wind velocity, and direction we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…For the exploration in hospitals, bacterial bioaerosol concentrations were higher at larger than those of fungi according to the result analyzing the air samples of different types of wards and operating theaters in hospital [16]. wastewater treatment plants revealed that the microscopic fungi accounted for the largest percentage followed by psychrophilic bacteria and mesophilic bacteria [20]. Interestingly, the study comparing the assemblage of fungal communities in units with visible mold and no visible mold found that the diversity of fungi in units with visible mold was less abundant as it was occupied with the classes Eurotiomycetes, Saccharomycetes, and Wallemiomycetes.…”
Section: The Community Structure In Hospitalsmentioning
confidence: 99%
“…For the exploration in hospitals, bacterial bioaerosol concentrations were higher at larger than those of fungi according to the result analyzing the air samples of different types of wards and operating theaters in hospital [16]. wastewater treatment plants revealed that the microscopic fungi accounted for the largest percentage followed by psychrophilic bacteria and mesophilic bacteria [20]. Interestingly, the study comparing the assemblage of fungal communities in units with visible mold and no visible mold found that the diversity of fungi in units with visible mold was less abundant as it was occupied with the classes Eurotiomycetes, Saccharomycetes, and Wallemiomycetes.…”
Section: The Community Structure In Hospitalsmentioning
confidence: 99%
“…Kolmogorov-Smirnov test was performed to determine the normality of the data (14). Also, the Kruskal-Wallis test was employed to compare the mean concentration of fungi among the units during the study (35). Spearman correlation coefficient was used to find the correlation between fungal and meteorological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, bacteria are one of the most studied bioaerosol components, showing average concentrations of 10 2 to 10 6 cells per cubic meter of air and with very high taxonomic diversity (Katsivela et al, 2017). In the air samples obtained in WWTP facilities, 25 species of Enterobacteriaceae were isolated, including the pathogenic bacteria Salmonella spp., Klebsiella pneumoniae and Escherichia coli (Michałkiewicz, 2018). Therefore, exposure to wastewater can cause illnesses such as gastrointestinal disorders, respiratory problems, skin disorders, fever, eye irritation, headaches, nausea, and fatigue (Manaia et al, 2018).…”
Section: Species Of Microorganisms Isolated From the Airmentioning
confidence: 99%